Challenges Faced by English Teachers in Online Teaching During the Covid-19 Pandemic - Adeliani, Resti; Rosdiana, Ihda (Jurnal Bahasa Inggris, 2021)
Online learning is learning that takes place without the need for teachers and students to physically meet. This study aims to find out the challenges of English teachers in online teaching during the pandemic. This research used a descriptive-qualitative research method. The participants were six teachers from two junior high schools in Tegal. The data were collected through questionnaires and interviews, thus validity and reliability were checked by Correlation Product Moment in SPSS. There were only 25 valid questions from the questionnaire which sig. (2-tailed)] < significant level (?) 0.05. The data were reliable because they had a Cronbach alpha > 0.6. There were five valid interview questions that the contents were appropriate for research purposes. The finding showed that 76% of teachers agreed that family support determined the successful learning process, 73% of teachers agreed that teacher readiness in online teaching was important, and 70% of teachers agreed that the availability of facilities, credit, and environmental conditions students must be available, 68% of teachers agreed that internet connectivity should be provided, 66% of teachers agreed that time management supports the effective learning process. Teachers must be ready and be able to overcome obstacles during online learning